Pre-surgical Provisional Prosthesis for Immediate Non-occlusal-loaded Flapless Implant - Inbarajan, Athiban (Cureus, 2017)
A 49-year-old patient reported for immediate replacement of missing maxillary anterior teeth with implant-retained prosthesis. Elevation of flap alters the mucosal level, causes discomfort, and delays the restorative procedure. To maintain the esthetics, flapless surgery was planned. Since placement of an implant is pre-planned in a predetermined site, fabrication of the prostheses before commencement of the surgery, especially when replacing the teeth in the anterior region, could be a viable option. This case report explains the method of fabrication of the provisional restoration for flapless surgery in the presurgical phase. The technique would avoid any micromotion and implant instability caused due to abutment preparation and impression procedure postsurgically.